2014
DOI: 10.5812/ircmj.11548
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Coagulation Factor V (Leiden) and Factor II (Prothrombin) Mutations with Stroke

Abstract: Background:Epidemiological studies indicate that over the past forty years, the stroke incidence rates has increased. Factors V and II mutations are established genetic-variant risk factors for venous thrombosis; however, their contribution to stroke is a controversial issue.Objectives:This study aimed to investigate the potential association of FV and FII mutations with stroke in an Iranian population.Patients and Methods:The study population consisted of 153 patients of different stroke subtypes (except cryp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…DOI: 10.15171/npj.2019. 16. reductase (MTHFR) genes (7). FVL refers to the G1691A (Arg506Gln; rs6025) mutation in exon 10 of the factor V (FV) gene.…”
Section: Lakkakula Vks Bhaskar*mentioning
confidence: 99%
“…DOI: 10.15171/npj.2019. 16. reductase (MTHFR) genes (7). FVL refers to the G1691A (Arg506Gln; rs6025) mutation in exon 10 of the factor V (FV) gene.…”
Section: Lakkakula Vks Bhaskar*mentioning
confidence: 99%
“…After duplicates were excluded, we assessed the titles and abstracts of the records and rejected articles that did not meet the inclusion criteria. At the end, there were 104 eligible studies in total—42 for FVL [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ], 30 for prothrombin [ 15 , 17 , 18 , 19 , 21 , 22 , 23 , 24 , 27 , 28 , 31 , 32 , 33 , 34 , ...…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the prevalence of Factor V heterozygous genotype was 2.6% in cases and 1.3% in the control subjects. [ 11 ] Another study reported from Greece also failed to observe the statistically significant association between Factor V Leiden gene polymorphism and risk of IS. [ 12 ] A study published by Hamedani in 2013, failed to observe the evidence of an association between Factor V Leiden and either overall IS or the different subtypes of IS.…”
Section: Discussionmentioning
confidence: 99%